The effect of solar tracker movement on the thermal performance of solar cooker using the Fresnel lens solar concentrator - Asrori Asrori; Sugeng Hadi Susilo; Kris Witono; Putu Wijaya Sunu (Politeknik Negeri Lhokseumawe, 2022)
Solar energy as renewable energy has great potential to supply the world's energy needs. Solar thermal energy can be used for domestic energy purposes (cooking and water heating). The purpose of this research is to develop, design and analyze the performance of a solar cooker from the concentration of direct normal irradiance (DNI) by the Fresnel lens on the receiver/absorber as a cooking vessel. One form of improving the performance of the Fresnel solar concentrator (FSC) is the addition of an automatic solar tracker installation using hydraulic actuators. The solar tracker is varied, every 5 and 10 minutes, respectively. The solar cooker performance test was conducted outdoors at the Mechanical Engineering Department of State Polytechnic of Malang (7.9553 oS and 112.6125 oE) in April 2021. The method used actual experimental research. The measurement of solar radiation uses a solar power meter SPM-1116SD and the tracker's movement. At the same time, the temperature parameters (water temperature, receiver wall temperature, focal point temperature, ambient temperature) are measured by the temperature data logger. The concentrated solar cooker type design uses a fresnel lens with a capture area of 0.785 m2 and a focal ratio of 0.88. The main components of this solar cooker design consist of: a large fresnel lens that functions as a concentrator of sunrays, a cone-shaped cooking stove as a solar collector (receiver), and a hydraulic actuator-type solar tracker unit. Initial tests showed that the solar radiation, In = 789.00 W/m2, obtained the focal point temperature at the receiver, Tf = 930.10°C. Meanwhile, the thermal efficiency (Th) of a solar cooker with a solar tracker that moves every 10 minutes and 5 minutes is 12.7% and 33.66%, respectively. The increase in the thermal efficiency of the solar cooker is very significant, which is 2.65 times. This shows that the more accurate and continuous movement of the tracker will increase the thermal efficiency of the designed Fresnel solar cooker.